Autoimmune Addison's Disease as Part of the Autoimmune Polyglandular Syndrome Type 1: Historical Overview and Current Evidence - Perniola, Roberto; Fierabracci, Alessandra; Falorni, Alberto (Frontiers in Immunology, 2021)
The autoimmune polyglandular syndrome type 1 (APS1) is caused by pathogenic variants of the autoimmune regulator (AIRE) gene, located in the chromosomal region 21q22.3. The related protein, AIRE, enhances thymic self-representation and immune self-tolerance by localization to chromatin and anchorage to multimolecular complexes involved in the initiation and post-initiation events of tissue-specific antigen-encoding gene transcription. Once synthesized, the self-antigens are presented to, and cause deletion of, the self-reactive thymocyte clones. The clinical diagnosis of APS1 is based on the classic triad idiopathic hypoparathyroidism (HPT) – chronic mucocutaneous candidiasis – autoimmune Addison’s disease (AAD), although new criteria based on early non-endocrine manifestations have been proposed. HPT is in most cases the first endocrine component of the syndrome, however APS1-associated AAD has received the most accurate biochemical, clinical and immunological characterization. Here is a comprehensive review of the studies on APS1-associated AAD, from initial case reports to the most recent scientific findings.